Pengaruh Model Pembelajaran Pbl Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII Mts Al-Ittihadiyah Percut - Rizki Aprina Nuranti; Hasratuddin Hasratuddin (Journal on Education, 2023)
This quasi-experimental research to determine the effect of the problem learning model on the mathematical communication abilities of class VIII of MTs Al-Ittihadiyah Percut. Mathematical communication ability is one of the basic mathematical abilities that every student should have. Through communication, there is a process of conveying ideas or ideas verbally or in writing so as to create an understanding. The population of this study were all class VIII students of MTs Al-Ittihadiyah Percut for the 2022/2023 academic year. The sample of this study were all students of class VIII MTs Al-Ittihadiyah there were class VIII-1 as the control class of 24 students and class VIII-2 as the experimental class of 26 students taken by saturated sampling technique. This research used the Nonequivalent Pretest-Posttest Control Group Design. Data analysis uses simple linear regression and Independent Sample T-Test. Based on the results of the research it was concluded that the effect of the problem based learning model was better than the normal learning model on students' mathematical communication abilities and the level of ability of students who were given the problem based learning model was better than students who were given the ordinary learning model.